Pembinaan Prestasi Pencak Silat Persaudaraan Setia Hati Terate Ranting Suradadi Kabupaten Tegal Tahun 2021 - Nugroho, Satrio Nanda; Setiawan, Ipang (Indonesian Journal for Physical Education and Sport, 2023)
The purpose of this study was to describe and determine the development of pencak silat achievements in Suradadi District, Tegal Regency. This research method is descriptive qualitative. Data collection techniques used interview, observation and documentation techniques. Data analysis techniques in this study used reduction analysis, data presentation and drawing conclusions. The results showed that; Mass, Breeding and Achievement has been going well. The coaching program is designed with the aim of introducing to the public, developing athletes' talents and giving birth to athletes who excel and have character. The conclusions that can be drawn from this research are indicators in the development of pencak silat achievement in the Suradadi Branch of PSHT, Tegal Regency, have been going well, there are only a few shortcomings that must be corrected. Suggestions that researchers can give are (1) there must be an effort to increase mass production; (2) pay more attention to the welfare of the trainers; (3) improving the quality of uncertified trainers